Suicidio en mujeres gestantes: vivencias y redes de apoyo para las familias que les sobreviven (2014)
ABSTRACT: To describe the experiences of the families of two pregnant women who committed suicide in the Department of Antioquia (Colombia) during 2010-2011. Methodology: a qualitative study using the hermeneutic phenomenological approach, specifically the case study method. Three to four interviews were conducted with each family. These interviews were later systematized using the Atlas ti software. Results: the category “family experience in the event of suicide: on how to become a learner” was found in the family of Bella, and two categories emerged from it: 1. “Her death affected us both internally and externally.” 2. “Between deafness and the power of the support networks.” In the family of Consentida, the “family experience: how to survive pain” category emerged, and additionally, two tendencies derived from it: 1. “Expanding and breaking networks.” 2. “Tying up loose ends.” Conclusions: the studied families have overcome the event as they have earned the recognition of collaborative, empowering and linking networks, which have remained throughout time. In their experience, the families have managed to distance themselves from the choice of their pregnant relatives and have thus bravely overcome their loss.